Early Alpine mountain bike events - Jean Saint-Martin; Frédéric Savre; Thierry Terret (Revue de Géographie Alpine)
During the 1980s, the diffusion of mountain biking in France underwent its first phase in mountain territories that discovered its socio-economic value. Over and beyond the structural and organisational aspects, the mountain bike also became a favoured medium for technological and social innovation. The aim here is to reflect upon the various underlying stakes of introducing, into Alpine territory, a new physical activity that required a two-wheeled vehicle and had its roots in the spirit and values of the already existing Californian practices. More than just an activity, mountain biking would become a market over the course of the decade. Its economic stakes would contribute to its imminent institutionalisation. Featuring among the vectors of its development, the first competitions and/or events played an essential role in establishing a special relationship between sport and tourism economy. As a new lease of life for a number of ski resorts undergoing crisis at the time, mountain biking offered the various actors (riders, cycle dealers, political and institutional leaders) an opportunity to valorise a technical and social innovation in mountain areas.